2022
DOI: 10.1089/ars.2021.0170
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Biology of Reactive Sulfur Species: Hydrolysis-Driven Equilibrium of Polysulfides as a Determinant of Physiological Functions

Abstract: Significance: Polysulfide species ( i.e., R-S n -R′, n > 2; and R-S n -H, n > 1) exist in many organisms. The highly nucleophilic nature of hydropersulfides and hydropolysulfides contributes to the potent antioxidant activities of polysulfide species that protect organisms against oxidative and electrophilic stresses. Recent Advances: Accumulating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…This high susceptibility of polysulfides (RSS n SR, n ≥1) to hydrolysis distinguishes them from disulfides (RSSR), which undergo a hydrolysis reaction only under strong alkaline conditions. The alkaline hydrolysis of RSSR leads to production of reduced thiol (RSH) and sulfenic acid (RSOH) [ 104 , 110 ]. At neutral pH, the equilibrium of the reaction of RSSR hydrolysis is shifted to the left, so disulfides at physiological pH rather do not undergo hydrolysis.…”
Section: Polysulfidesmentioning
confidence: 99%
See 3 more Smart Citations
“…This high susceptibility of polysulfides (RSS n SR, n ≥1) to hydrolysis distinguishes them from disulfides (RSSR), which undergo a hydrolysis reaction only under strong alkaline conditions. The alkaline hydrolysis of RSSR leads to production of reduced thiol (RSH) and sulfenic acid (RSOH) [ 104 , 110 ]. At neutral pH, the equilibrium of the reaction of RSSR hydrolysis is shifted to the left, so disulfides at physiological pH rather do not undergo hydrolysis.…”
Section: Polysulfidesmentioning
confidence: 99%
“…It has been shown that various alkylating reagents including IAA, NEM, mBrB or dimedone can enhance the hydrolysis of polysulfides [ 104 , 112 ]. During the hydrolysis, there is some equilibrium between RSS n SR and its products, i.e.…”
Section: Polysulfidesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, small molecule RSS donors have shown high efficacy in animal models for conditions ranging from cardiovascular disease and ischemia/reperfusion injury to gastrointestinal inflammation and wound healing. [23][24][25] Similarly, contemporary investigations have led to the discovery of new fundamental chemistry of persulfides and polysulfides, [26][27][28] new approaches for responsive RSS delivery, [29][30] and new interconnectivities with other small signaling molecules. [31][32][33][34][35] An attractive approach for sulfane sulfur delivery would be to use systems with only S 0 atoms.…”
Section: Introductionmentioning
confidence: 99%